2014
DOI: 10.1039/c4ob01921k
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic enantioselective α-amination of 5-substituted rhodanines: an efficient approach to chiral N,S-acetals

Abstract: We report a highly efficient approach to constructing chiral N,S-acetals using 5-substituted rhodanines as sulfur-bound pronucleophiles catalyzed by natural cinchona alkaloids quinine or quinidine. This α-amination reaction has a broad substrate scope, and the products featuring both rhodanine and N,S-acetal structural motifs were obtained in high yields and excellent enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Then, Wang et al. developed a quinine mediated enantioselective α‐amination of 5‐substituted rhodanines for the construction of chiral N , S ‐acetal motifs . With 2‐aryl‐5‐methylthiazol‐4‐ones as sulfur‐bound pronucleophiles, Palomo et al.…”
Section: Methodsmentioning
confidence: 99%
“…Then, Wang et al. developed a quinine mediated enantioselective α‐amination of 5‐substituted rhodanines for the construction of chiral N , S ‐acetal motifs . With 2‐aryl‐5‐methylthiazol‐4‐ones as sulfur‐bound pronucleophiles, Palomo et al.…”
Section: Methodsmentioning
confidence: 99%
“…In 2014, Wang et al. developed a chiral tertiary amine catalyzed α‐amination of 5‐substituted rhodanines to furnish chiral N , S ‐acetals in high yields and enantioselectivities (Scheme D) . The investigation of the azodicarboxylate partner indicated that the ester moiety has a profound effect on the asymmetric induction.…”
Section: Methodsmentioning
confidence: 99%
“…The organocatalytic enantioselective α‐amination of 5‐substituted rhodanines are established by Wang et al. to furnish chiral N,S ‐acetals in high yields and enantioselectivities (Scheme F) . The evaluation of the azodicarboxylate partner reveals that the ester moiety has a profound effect on the asymmetric induction.…”
Section: Methodsmentioning
confidence: 99%